2001
DOI: 10.1083/jcb.152.6.1219
|View full text |Cite
|
Sign up to set email alerts
|

The Nc1/Endostatin Domain ofCaenorhabditis elegansType Xviii Collagen Affects Cell Migration and Axon Guidance

Abstract: Type XVIII collagen is a homotrimeric basement membrane molecule of unknown function, whose COOH-terminal NC1 domain contains endostatin (ES), a potent antiangiogenic agent. The Caenorhabditis elegans collagen XVIII homologue, cle-1, encodes three developmentally regulated protein isoforms expressed predominantly in neurons. The CLE-1 protein is found in low amounts in all basement membranes but accumulates at high levels in the nervous system. Deletion of the cle-1 NC1 domain results in viable fertile animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
150
2
8

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(168 citation statements)
references
References 60 publications
5
150
2
8
Order By: Relevance
“…Soluble monomeric endostatins could be obtained, however, from insect cells (4), yeast (17,19), and mammalian cells (20)(21)(22) but they may show subtle differences in conformation and posttranslational modifications. Domain NC1 could be also produced in mammalian cells and was shown to assemble noncovalently into a 100-kDa homotrimer as demonstrated for mouse collagens XVIII (20) and XV (21) and the C. elegans homolog (15).…”
Section: Structure and Binding Properties Of Nc1 Domains And Endostatinsmentioning
confidence: 97%
See 1 more Smart Citation
“…Soluble monomeric endostatins could be obtained, however, from insect cells (4), yeast (17,19), and mammalian cells (20)(21)(22) but they may show subtle differences in conformation and posttranslational modifications. Domain NC1 could be also produced in mammalian cells and was shown to assemble noncovalently into a 100-kDa homotrimer as demonstrated for mouse collagens XVIII (20) and XV (21) and the C. elegans homolog (15).…”
Section: Structure and Binding Properties Of Nc1 Domains And Endostatinsmentioning
confidence: 97%
“…Some of the capillaries in these tissues were collapsed and contained degenerated endothelial cells, and it was concluded that collagen XV has a structural rather than regulatory function. A deletion mutation of the collagen XV/XVIII homolog in C. elegans that removed most of the NC1 domain also did not interfere with basement membrane assembly, but caused major defects in neuronal migration and axon guidance (15). Ectopic expression of NC1 rescued the cell migration defects, whereas the ectopic expression of the endostatin module does not rescue but dominantly cause the defects.…”
Section: Collagens XV and Xviiimentioning
confidence: 97%
“…This domain is the most highly conserved between the vertebrate and C. elegans proteins. cle-1 generates at least three protein isoforms by utilizing three promoters and alternative splicing (Figure 11; Ackley et al, 2001). The two longer CLE-1 isoforms are synthesized by neurons, an unusual situation for any collagen.…”
Section: Collagen Type XVIIImentioning
confidence: 99%
“…The major C. elegans basement membrane proteins and their receptors are listed in Tables 1 and 2. Collagen IV α1 emb-9 1 Emb (2-3X) Guo et al, 1991;Gupta et al, 1997 Collagen IV α2 let-2 2 Emb (2-3X) Sibley et al, 1993Sibley et al, , 1994 Collagen XVIII cle-1 4 Neuro, gonad morph Ackley et al, 2001Ackley et al, , 2003 Fibulin-1 fbl-1 2 Gonad morph Hesselson et al, 2004;Kubota et al, 2004 Hemicentin Osteonectin/SPARC ost-1 1 Acc (L1-L2) Fitzgerald and Schwarzbauer, 1998 Papilin ppn-1 3 Emb (hyp enclosure) Kramerova et al, 2000 Perlecan unc-52 >5 Pat Rogalski et al, 1993Rogalski et al, , 1995 In C. elegans, BMs surround all internal tissue surfaces, covering body wall muscles, pharynx, intestine, gonad and the pseudocoelomic face of the hypodermis. The BM covering the ventral and dorsal nerve cords interposes between motor neurons and muscles and forms part of the neuromuscular junctions, as is also the case in vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins are found in the ECM and basal laminae [14,15], and both are characterized by (a) an N-terminal laminin globular ''G'' domain; (b) a C-terminal peptide with antiangiogenic properties (endostatin in col 18a1 and restin in col 15a1), with these two domains flanking; (c) a central region made up of several collagen repeats interrupted by nonhelical regions [15,16]. A single member of this family is known from Drosophila melanogaster (Genbank ID: CG33171), which lacks the N-terminal laminin domain [17], and a single member from C. elegans (cle-1, C36B1.1) [18,19]. The high degree of conservation between col 15a1 and col 18a1 suggests that these two collagens are functionally related [15,20], and the similarity in their genomic structure indicates that col 15a1 and col 18a1 derive from the same ancestral gene [14].…”
Section: Introductionmentioning
confidence: 99%